Dissolution and Characterization of Biofunctional Keratin Particles Extracted from Chicken Feathers - Sharma, Swati; Gupta, Arun; Syed Mohd Saufi, Tuan Chik; Chua, Gek Kee; Poddar, Pradeep Kumar (IOP Publishing, 2017)
In the present study chicken feathers were hydrolyzed in alkaline environment. The pH value of feather hydrolyzed solution was adjusted according to the principle of isoelectric precipitation. Three kinds of precipitates of keratin polypeptide were collected at pH of 3.5, 5.5 and 7.5 respectively. The keratin solution were freeze dried and denoted as FKP1, FKP2, FKP3 respectively. All keratin particles possessed smooth, uniform and round surface by scanning electron microscope (SEM). FKP1, FKP2 and FKP3 had higher glass transition temperature examined by thermogravimetry (TG). Fourier transform infrared spectroscopy (FTIR) revealed that the extracted keratin retained the most of protein backbone, with the breakage of disulfide cross-links and hydrogen bonds.